Nursing Acute Pain in Patients With Bladder Cancer: A Case Study - Frans Zizka Hervira (Chakra Brahmanda Lentera Institute, 2022)
Background: Severe pain in the lower right abdomen is often found in bladder cancer patients. Bladder cancer is a complex disease associated with high morbidity and mortality if not treated optimally. Patients who suffer from bladder problems say that the influence of medical personnel influences the most significant role in pain control. Nursing care for acute pain in patients with bladder cancer is still unknown. This study aims to describe nursing care for acute pain in bladder cancer patients. Methods: This research uses a case study design. Data collection from assessment to nursing evaluation was carried out in the Punai room of the Simpang Lima Gumul Hospital, Kediri Regency, in December 2021. The bladder patient was observed or treated for at least two days. Data collection techniques used were interviews, observation, and documentation. Data analysis was carried out using narrative analysis. Results: Mr. R, the main complaint felt by the patient is a pain in the lower right abdomen penetrating to the back. The nursing diagnosis in the case of Mr. R is the actual diagnosis of acute pain associated with physical injury (D.0077). Nursing intervention for Mr. R was compiled based on the diagnosis of acute pain using pharmacological techniques. Conclusion: The nursing problems Mr. R resolved after 48 hours of nursing intervention. The patient shows a decreased pain level with a pain scale of 2, and the patient plans KRS after 2 days the problem is resolved.